2009
DOI: 10.1186/1475-2840-8-58
|View full text |Cite
|
Sign up to set email alerts
|

Elevated plasma levels of TNF-alpha and Interleukin-6 in patients with diastolic dysfunction and glucose metabolism disorders

Abstract: BackgroundDiabetes mellitus (DM) has reached epidemic proportions and is an important risk factor for heart failure (HF). Left ventricular diastolic dysfunction (LVDD) is recognized as the earliest manifestation of DM-induced LV dysfunction, but its pathophysiology remains incompletely understood. We sought to evaluate the relationship between proinflammatory cytokine levels (TNF-alpha, IL-6) and tissue Doppler derived indices of LVDD in patients with stable coronary artery disease.MethodsWe enrolled 41 consec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
74
0
8

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(85 citation statements)
references
References 24 publications
3
74
0
8
Order By: Relevance
“…A positive correlation between TNF-alpha and BMI has also been reported [137]. Recently, it was reported that elevated plasma levels of TNF-alpha are associated with left ventricular diastolic dysfunction, which is one of the earliest manifestations of left ventricular dysfunction due to diabetes mellitus [138], while administration of TNF-alpha inhibitors leads to an increase of HDL levels [39]. It has been stressed that TNF-alpha is involved in the pathogenesis of metabolic syndrome [1,46].…”
Section: Tumor Necrosis Factor-alpha (Tnf-alpha)mentioning
confidence: 99%
“…A positive correlation between TNF-alpha and BMI has also been reported [137]. Recently, it was reported that elevated plasma levels of TNF-alpha are associated with left ventricular diastolic dysfunction, which is one of the earliest manifestations of left ventricular dysfunction due to diabetes mellitus [138], while administration of TNF-alpha inhibitors leads to an increase of HDL levels [39]. It has been stressed that TNF-alpha is involved in the pathogenesis of metabolic syndrome [1,46].…”
Section: Tumor Necrosis Factor-alpha (Tnf-alpha)mentioning
confidence: 99%
“…При отсут-ствии различий базовых уровней ИЛ-6 в группах его динамика была более выражена во II группе. С гиперпро-дукцией ИЛ-6 ассоциируется развитие диастолической дисфункции ЛЖ [39]. В исследованиях снижение уровня ИЛ-6, ФНО-α было описано только у респондеров [24,31].…”
Section: Discussionunclassified
“…Уровень ФНО-α увеличивается в кро-ви при различных сердечно-сосудистых заболева-ниях, в том числе при миокардите, инфаркте миокар-да и застойной сердечной недостаточности, которые до-статочно часто встречаются у больных РА [14]. Иссле-дования на мышах показали, что ФНО-α может уси-ливать апоптоз, гипертрофию, воспалительную реак- …”
Section: Discussionunclassified